KONSTRUKSI POLA VISUAL DALAM PEMBANGUNAN IMPRESI KOMEDI MELALUI TEKNIK EDITING SINETRON PREMAN PENSIUN 3 (Studi Kasus: Episode 7, 9, 11 dan 18) - Aji, Fajar (Institut Seni Budaya Indonesia Bandung, 2017)
Sinetron as well as films are formed from narrative and cinematic elements. Editing is one of the cinematic elements which can conveys the impression of atmosphere in the film throught constructed by visual. Sinetron Preman Pensiun 3 with the comedy genre trying to convey a paralleled scene. Based on the phenomenon, this research aims is conducted to find out the development of comedy impression through editing techniques. The result shows that development of comedic impression is capable constructed through editing techniques. Editing aspect provides information in detail and the impression of humor or funny atmosphere, while the humor theory illustrated the universal characteristics that can provide a comedy charges.